Spontaneous cholecystocutaneous fistula: a rare complication of gallbladder disease - Cruz Junior, Ruy Jorge; Nahas, Jorge; Figueiredo, Luiz Francisco Poli de (São Paulo Medical Journal, 2006)
CONTEXT: Spontaneous cholecystocutaneous abscess or fistula is an extremely uncommon complication secondary to cholecystitis. Over the past 50 years fewer than 20 cases of spon- taneous cholecystocutaneous fistulas have been described in the medical literature. We here report a case of subcutaneous gallstone as a rare clinical presentation of the already uncommon cholecystocutaneous fistula. CASE REPORT: An 81-year-old man presented with a large subcutaneous abscess in the right subcostal area with surrounding cellulitis and crepitus. An abdominal computed tomography scan showed two subcutaneous gallstones and communication between the abscess and the gallbladder. Cholecystectomy was performed and the abdominal wall abscess was drained ex- ternally. This case report demonstrates that main- taining a high degree of suspicion of this rare entity is helpful in achieving correct preoperative diagnosis, and that computed tomography scan should be performed in all cases of unexplained abdominal wall suppuration or cellulitis.